The potential risk factors of early-onset post-stroke depression from immuno-inflammatory perspective - Chen, Hengshu; Liu, Fan; Sun, Dongren; Zhang, Jingyuan; Luo, Shihang; Liao, Qiao; Tian, Fafa (Frontiers in Immunology, 2022)
Background Mounting evidence strongly uncovered that peripheral immuno-inflammatory response induced by acute stroke is associated with the appearance of post-stroke depression (PSD), but the mechanism remains unclear. Methods 103 stroke patients were assessed at 2 weeks after onset using Diagnostic and Statistical Manual of Mental Disorders, 5th edition and then divided into PSD and non-PSD groups. Polymorphisms of inflammatory molecules (interleukin [IL]-1β, IL-6, IL-10, IL-18, tumor necrosis factor-α [TNF-α], interferon-γ [IFN-γ] and C-reactive protein [CRP]), complete blood count parameters, splenic attenuation (SA) and splenic volume (SV) on unenhanced chest computed tomography, demographic and other clinical characteristics were obtained. Binary logistic regression model was used to analyze the associations between inflammation-related factors and the occurrence of PSD at 2 weeks after stroke. Results 49 patients were diagnosed with PSD at 2 weeks after onset (early-onset PSD). The C/T genotypes of CRP rs2794520 and rs1205 were less in PSD group than non-PSD group (both adjusted odds ratio = 3.364; 95%CI: 1.039-10.898; p = 0.043). For CRP rs3091244, the frequency of G allele was higher (80.61% vs. 13.89%) while the frequency of A allele was lower (6.12% vs. 71.30%) in PSD patients than non-PSD patients (χ2 = 104.380; p<0.001). SA of PSD patients was lower than that of non-PSD patients in the presence of CRP rs2794520 C/T genotype and rs1205 C/T genotype (both t = 2.122; p = 0.039). Peripheral monocyte count was less in PSD group than non-PSD group (adjusted odds ratio = 0.057; 95%CI: 0.005-0.686; p = 0.024). Conclusions CRP polymorphisms, SA based on CRP genotype, and peripheral monocytes are associated with the risk of early-onset PSD, suggesting peripheral immuno-inflammatory activities elicited by stroke in its aetiology.